Effects of Conventional Method of Freezing on Post Thaw Characteristics of Dog Spermatozoa - Sabarinathan, A.; Sathiamoorthy, T.; Kulasekar, K.; Parthiban, M.; Rangasamy , S.; Gopikrishnan, D. (International Journal of Livestock Research, 2018)
Semen samples were collected from twenty healthy and sexually mature dogs of different breeds by digital manipulation. Out of twenty dogs fifteen had sired a litter before and remaining five dogs had not been tested. The physical and morphological characteristics of fresh semen samples viz. volume, colour, consistency, pH, percentage of gross motility, spermatozoal concentration, percentage of live, abnormality, acrosomal integrity and plasma membrane integrity of sperms were evaluated. The semen samples with acceptable quality were cryopreserved with Tris egg yolk extender by conventional freezing method. The physical and morphological characteristics such as post thaw motility, live and dead, abnormality, acrosomal integrity and plasma membrane integrity of frozen semen were evaluated 24 hours after freezing. The effects of conventional method of freezing on spermatozoa were assessed.